Прогнозная оценка трансграничного переноса радионуклидов вследствие прохождения смерча над водоемом-охладителем ЧАЭС - Талерко, Н.Н.; Гаргер, Е.К.; Кузьменко, А.Г. (Проблеми безпеки атомних електростанцій і Чорнобиля, 2013)
Выполнен прогноз возможного радиоактивного загрязнения территории Беларуси и России вследствие
атмосферного переноса радионуклидов, поднятых с осушенной территории водоема-охладителя ЧАЭС при
прохождении смерча в чернобыльской зоне отчуждения. Расчеты проведены с помощью комплекса моделей,
включающего концептуальную модель смерча, мезомасштабную диффузионную модель атмосферного перено-
са примеси и блока дозиметрических моделей. Получено, что в ближайших населенных пунктах Беларуси и
России увеличение плотности выпадений не превысит 1 - 2 % по сравнению с фактическим. Доза облучения для
жителей Беларуси не превысит 1 мкЗв, России – 10⁻² мкЗв. Виконано прогноз можливого радіоактивного забруднення території Білорусі та Росії внаслідок атмосферного перенесення радіонуклідів, піднятих з осушеної території водойми-охолоджувача ЧАЕС при проходженні смерчу в чорнобильській зоні відчуження. Розрахунки проведено за допомогою комплексу моделей,
що включає концептуальну модель смерчу, мезомасштабну дифузійну модель атмосферного перенесення
домішки та блока дозиметричних моделей. Отримано, що в найближчих населених пунктах Білорусі та Росії
збільшення щільності випадінь не перевищить 1-2 % у порівнянні з фактичним. Доза опромінення для жителів
Білорусі не перевищить 1 мкЗв, Росії -10⁻² мкЗв. According the design documentation for the Chernobyl NPP Cooling Pond (CP) decommissioning a forecast of possible radioactive contamination of the territory of Belarus and Russia due to radionuclides resuspension followed a tornado passage over the CP drained part are made. The calculations were performed using a set of models, including the conceptual model of a tornado, the mesoscale atmospheric diffusion model of pollutant transport LEDI and dosimetric models. The activity raised by a tornado vortex of intensity F3 from the CP drained part was assessed as 13.9 TBq ¹³⁷Cs, 2,47 TBq ⁹⁰Sr, 0.0248 TBq Pu. Depending on the chosen meteorological scenario an maximal additional density deposition on the territory of Belarus (in Polesye State Radiation Ecological Reserve) was assessed as 35 kBq m⁻² ¹³⁷Cs, 6 kBq m⁻² ⁹⁰Sr and 0,06 kBq m⁻² Pu, whereas in the nearest settlements of Belarus and Russia - 5 - 9 kBq m⁻² ¹³⁷Cs, 1.0 – 1.7 kBq m⁻² ⁹⁰Sr and 10 – 17 Bq m⁻² Pu, i.e. it isn’t exceed 1⁻² % of the actual one. The radiation dose to the people of Belarus will not exceed 1 mSv, Russia - 10⁻² mSv. Hence, the safety analysis showed that a tornado passage over the CP will not result in an unacceptable dose to individuals in Belarus and Russia.